ANTIOXIDANT AND ANTIPROLIFERATIVE POTENTIALS OF MARINE ACTINOMYCETES - P., Nagaseshu; V., Gayatridevi; B., Anil Kumar; Kumari, Seema; G., Murali Mohan; Malla, Rama Rao (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of present studyis to isolate and characterize a novel actinomycetes strain from marine sediments collected at Kakinada coast. To evaluate antioxidant and antiproliferative activities of the crude methanolic extract of isolated actinomycetes. Methods: Actinomycetes was isolated from marine sediments collected at Kakinada coast using starch casein agar. Morphological, biochemical and molecular characterization was performed and the crude methanolic extract was used for determination of in vitro antioxidant activity and antiproliferative activity against MDA-MB 231 breast cancer cells. Results: The crude methanolic extract exhibited significant antioxidant activity with IC50 value in the range of 30-46 µg/ml in different radical scavenging assays. Moreover, the extract showed concentration dependent cytotoxicity against triple negative breast cancer cell line, MDA-MB 231 with IC50 of 42.5µg/ml. The extract also inhibited cell proliferation with IC50 value 44.1 µg/ml probably by arresting cell cycle at S phase. The antioxidant activity of the extract was strongly correlated with cytotoxic and antiproliferative activity. Conclusion: The isolated marine actinomycetes can be the potential source of antioxidants with the anticancer property.